1982
DOI: 10.1007/bf02796428
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a cell line (SW756) derived from a human squamous carcinoma of the uterine cervix

Abstract: An established cell line, SW756, derived from a primary squamous carcinoma of the uterine cervix is described by its morphology, ultrastructure, karyotype, genetic signature analysis, HLA typing, and tumorigenesis in the nude mouse. Cultured cells obtained from the SW756 derived nude mouse tumor also were studied for chromosome and isozyme markers. The original tumor was poorly differentiated carcinoma with minimal keratinization and is compared with that occurring in the nude mouse after the cultured cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Cell lines Cells of the cervical carcinoma lines HeLa, C4-1 (Auersperg and Hawryluk, 1962) and SW756 (Freedman et al, 1982) were grown in monolayer cultures in Eagle's minimum essential medium containing 10% fetal calf serum. Construction of cDNA libraries and screening Cytoplasmic RNA was prepared from tissue culture cells as described (Freese et al, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…Cell lines Cells of the cervical carcinoma lines HeLa, C4-1 (Auersperg and Hawryluk, 1962) and SW756 (Freedman et al, 1982) were grown in monolayer cultures in Eagle's minimum essential medium containing 10% fetal calf serum. Construction of cDNA libraries and screening Cytoplasmic RNA was prepared from tissue culture cells as described (Freese et al, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…Derivation of the HPV-immortalized and ras-transformed cell lines (Woodworth et al, 1988;DiPaolo et al, 1989) and cervical carcinoma-derived cell lines C-4I, C-4II, CaSki, C-33A, HeLa, HT-3, SiHa (all from the American Type Culture Collection), QGH and QGU (Shirasawa et al, 1987) and SW756 (Freedman et al, 1982) have been described previously. Normal ectocervical cells and the cell line CX16-2 were grown in serum-free MCDB153-LB medium (Pirisi et al, 1987).…”
Section: Cell Culturementioning
confidence: 99%
“…The cell lines used were C4-1 and C4-2 (26), which were derived from the same biopsy specimen of a squamous cell carcinoma and are therefore of identical clonal origin (27), HeLa, which was derived from an adenocarcinoma of the cervix (28,29), and SW 756, more recently established from a squamous cell carcinoma (30). We found that depending on the origin of the cell line and the chromosomal integration site of the viral DNA, dexamethasone treatment modified the transcription rate of HPV genes differently.…”
mentioning
confidence: 99%